The Implementation of School-Based Management in Improving Quality of Education in Primary School - framz hardiansyah (Kelola: Jurnal Manajemen Pendidikan, 2022)
Quality education is an absolute requirement to achieve national development goals; thus, education will produce superior and competitive human resources. Many government efforts improve the quality of education, among others, with regional autonomy or decentralization, which produces school-based management in the world of education. School-Based Management enables schools to be more independent through the granting of authority (autonomy), greater flexibility for schools in managing resources, and encouraging the participation of school members and the community to improve the quality of education. This research aims to determine how to implement school-based management to improve the quality of education in elementary schools. This research uses a qualitative descriptive method with data collection through interviews and observation. The subjects in this study were principals, teachers, school committees, community leaders, and stakeholders. This data analysis used data reduction, data presentation, and data validation (concluding). The results of the research findings indicate that the implementation of school-based management in improving the quality of education in elementary schools has been going well; the activeness of the school committee evidence this by providing suggestions/considerations, supporters, controllers, and mediators, the direct participation of parents in the planning and implementation of the program. In schools as well as management of curriculum and teaching programs, management of students, management of educators and education staff, and management of facilities and infrastructure are carried out well.